Wild edible plants in rural home gardens: livelihoods, perceptions, economic value & traditional knowledge - Mothupi, Frans Makwena (Rhodes University, Faculty of Science, Department of Environmental Science)
The prevalence of hunger and malnutrition has been steadily increasing in the world over the past decades. The rate of food insecurity was further exacerbated by the COVID 19 pandemic which plunged millions more into hunger as a result of a recovering economy and high food prices. These challenges are mostly experienced in Africa and are estimated to worsen in this region already affected by conflict, poor healthcare, and natural disasters such as floods and droughts. The green revolution in the 1960's elevated agricultural production to play a pivotal role in the provision of food. However, production focused mainly on the cultivation of staple crops such as rice, wheat, and maize. The reliance on these crops has contributed to the lack of micronutrient intake and consumption of non-diverse diets. Wild edible plants (WEPs) which previously formed a significant part of indigenous people's diet, have been regarded as an important food source crucial for the alleviation of malnutrition and micronutrient deficiencies. Despite their nutritional qualities, they are often ignored, overlooked, and undermined by agricultural programmes and food security interventions. Additionally, WEPs are largely absent in modern diets, they are often surrounded by negative perceptions, they are economically undervalued, and the indigenous knowledge of these species is under threat. As a result, this study regards WEPs as important resources that can significantly contribute to improved livelihood outcomes such as income, food security and good health. Using the Sustainable Livelihoods Framework, this study evaluated the contribution of WEPs to sustaining livelihoods, providing economic value, and examined how WEPs are perceived as well as the relationship between their knowledge and consumption in rural areas. This study was conducted in rural villages that are under the jurisdiction of the Moletjie and Matlala tribal authorities in the Polokwane and Aganang local municipalities, South Africa. Qualitative and quantitative research methods were employed for data collection. A total of 356 participants were interviewed for this study. Firstly, in-depth interviews were conducted with 20 elderly participants (Chapter 2). Semi-structured interviews were conducted with a total of 120 participants stratified by age, gender, and income groups (Chapter 3). A total of 96 household surveys were conducted in selected villages, this was complemented by direct observations and field surveys of the home gardens (Chapter 4). Questionnaires and freelists were administered to a total of 120 participants also stratified by age, gender, and income groups to collect data on indigenous knowledge of WEPs (Chapter 5). Thematic analysis were performed for interview data (Chapter 2) and data were summarised, descriptive statistics, chi square tests (Chapter 3), Kruskal-Wallis tests (Chapter 4), ANOVA tests and correlation tests (Chapter 5) were performed using SPSS software. The findings show that there has been a major nutrition transition characterised by changed meal composition, patterns, and frequency relating to the consumption of WEPs. The changes can be attributed to increasing western influence characterised by rising urbanisation, western lifestyle of church, school, and employment in an income-based economy dependent on retail stores to fulfil their daily dietary needs. Despite this, WEPs are still valuable to rural people, this is indicated by the fact that traditional foods are made optional at some modern and traditional celebrations. Overall, most of perceptions (65.6%) regarding the consumption of WEPs were positive. The overwhelming majority of respondents agreed or strongly agreed that preparations from the local WEPs are relatively more tasty (98.3%), healthy (96.6%), nutritious (86.7%), and better represent the traditional foods (94.1%). Additionally, participants perceived WEPs to have health benefits in that they have medicinal properties to help prevent diseases, are a good source of energy, highly nutritious and they give strength. Despite these benefits and positive perceptions, most participants expressed doubt over the commercial success of WEPs if they were to compete with cultivated crops in the market. As a result, they perceive the future of WEPs to be bleak as 95% of participants believe that their consumption is in decline. This can be largely attributed to deagrarianisation, climate change, and preference of cultivated foods by the youth. The study also showed that a diversity fruits and vegetables are available in rural home gardens, with cultivated fruits grown in abundance and WEPs available in almost all households (98%). WEPs represented 34% of the total estimated economic value of plants available in rural home gardens. Most of the home gardens produce food to supplement household food supply with only a few households engaged in trading. The trading of WEPs was recorded in 9% of the home gardens while 16% sold cultivated fruits and/or vegetables. Challenges such as lack of water and poor rainfall are shocks which affect the availability, richness, and abundance of home garden produce. WEPs are generally well known in rural areas as participants listed an average of 8.4±2.4 species. There was a significant statistical difference between the number of species listed by age group (p = 0.009) with the elderly listing a higher average number of species (9.3±2.6) compared to adults (8.1±2.5) and the youth (7.8±1.7). Vangueria infausta, Sclerocarya caffra, Ximenia caffra, Amaranthus retroflexus L. retroflexus, Citrullus lanatus,and Cleome gynadra where among the top listed species. There was also a significant positive correlation between the number of listed fruits with number of listed vegetables. The study also found a positive correlation between knowledge of WEPs and consumption. Most of the knowledge about WEPs was learned from a family member (89%), own observation (86%), a village elder (75%). This knowledge was mostly acquired from childhood through oral tradition (63%) and through participation (21%), and consumption (12%).
Keywords: Wild plants, Edible -- South Africa; Sustainable livelihood; Traditional knowledge; Economic value; Food security -- South Africa